Cyborg - Pyun, Albert; Richter, Deborah; Vincent Klyn; Alex Daniels; JeanClaude Van Damme (USA Golan-Globus Productions, 1989)
Set in a post-apocalyptic future where starvation and disease are plaguing the few remaining inhabitants of Earth. Scientists are close to discovering a cure for the plague that is sweeping the country. Gibson Rickenbacker is a strong fighter who leads a group to Atlanta to gain information needed for the cure, along the way attempting to avoid the villains.
A martial artist hunts a killer in a plague-infested urban dump of the future.
Kitty Chalmers
Languages : English, French, Spanish, Italian Subtitles : English, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese, Danish, Finnish, Greek, Hindi, Hungarian, Icelandic, Norwegian
Keywords: SciFi; Action